TRAINING ON DESIGNING BEST PRACTICE SCHOLARLY WRITING TO ENHANCE ENGLISH TEACHERS’ PROFESSIONAL DEVELOPMENT - Rina Husnaini Febriyanti; Hanna Sundari; Oom Rohmah Syamsudin; Rifari Baron (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2025)
Teacher professional development is essential for a teacher to achieve teaching goals, whether in implementing the instruction or pedagogic dimensions. One of the efforts in developing teaching professionalism is designing a scholarly writing. However, in crafting a scholarly writing, a teacher encounters several challenges and difficulties, such as time management, research methodologies, designing instruments, generating research ideas or topics, etc. These issues were found in the Subject Teacher Discussion Forum (MGMP) of English teachers in Bekasi City as partners in this community service. Hence, in this community service event, the teachers were trained to design a scholarly writing in Best Practice research and the Situation, Task, Action, and Result (STAR) technique. The community service employed the Community-Based Participatory Research (CBPR) method. The result of the community service program (PkM) revealed that almost all the participants were motivated to write a scholarly writing.